CRITICAL PERIOD OF MUNGBEAN (PHASEOLUS RADIATUS L.) TO WEED COMPETITION - I.H. UTOMO (SEAMEO BIOTROP, 1989)
A field experiment was conducted to study the critical period of weed control on the crop of mungbean (Phaseolus radiatus L.). The studies were done in the field of BIOTROP Experimental Station with the natural existing weed population. It was found that the critical period of mungbean to weed competition was from 3-6 weeks after planting.